Penyuluhan Praktik Kesehatan dan Keselamatan di Tempat Kerja bagi Calon Teknisi Akuntansi Muda - Brabo, Nora Andira; Meidiyustiani, Rinny; Rahmat, Hayatul Khairul; Iswati, Heni (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
In the era of globalization and rapid industrial development, occupational health and safety (OHS) practices are important aspects that must be understood and implemented by all workers, including accounting technicians. Therefore, it is important that a community service activity that aims to help prospective young accounting technicians create a safe and productive work environment and pay more attention to the health and safety of workers can run smoothly and participants understand the material provided.